Hybridoma cell lines secreting monoclonal antibodies against equine infectious anemia virus - Horenstein, A. L.; Glait, H. M.; Koss, Amalia (Elsevier, 1987)
Fil: Koss, Amalia Comisión Nacional de Energía Atómica; Argentina